Plant Unsaturated Fatty Acids: Multiple Roles in Stress Response - He, Mei; Ding, Nai-Zheng (Frontiers in Plant Science, 2020)
Land plants are exposed to not only biotic stresses such as pathogen infection and herbivore wounding, but abiotic stresses such as cold, heat, drought, and salt. Elaborate strategies have been developed to avoid or abide the adverse effects, with unsaturated fatty acids (UFAs) emerging as general defenders. In higher plants, the most common UFAs are three 18-carbon species, namely, oleic (18:1), linoleic (18:2), and α-linolenic (18:3) acids. These simple compounds act as ingredients and modulators of cellular membranes in glycerolipids, reserve of carbon and energy in triacylglycerol, stocks of extracellular barrier constituents (e.g., cutin and suberin), precursors of various bioactive molecules (e.g., jasmonates and nitroalkenes), and regulators of stress signaling. Nevertheless, they are also potential inducers of oxidative stress. In this review, we will present an overview of these roles and then shed light on genetic engineering of FA synthetic genes for improving plant/crop stress tolerance.